High Risk of Failed Skin Graft on Major Burn Patients with Complication of Hypernatremia - Hariani, Lynda; Budi, Agus Santoso; Wulandari, Ephora Christina (Folia Medica Indonesiana, 2021)
The rate of failed skin graft in Dr. Soetomo General Academic Hospital Surabaya was around 26% of the cases, and it became a concern because skin graft was the main procedure to close large burn wounds. Many problems might affect this event; one of them was electrolyte imbalance. Hypernatremia was found in major burn patients. This condition disrupted the wound healing process of skin graft. This cross-sectional study evaluated patients with burns admitted to the Burn Centre of Dr. Soetomo Hospital between January 2014 and December 2018. 143 subjects participated in this study. Hypernatremia was found in 16% of all subjects (23 subjects), 19% with hypernatremia (28 subjects), and the majority of it, 65% with normonatremia (92 subjects). This study found that the risk of failed skin graft was higher on hypernatremia than normonatremia subjects. This risk was higher if the skin graft procedure took more than 10%.